STUDENTS’ LEARNING STRATEGIES IN ENGLISH COMMUNICATION AT IKIP MATARAM - Salim, Agus (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2017)
This study is aimed at find out the students? learning strategies in English communication.Due to the learning strategies, the researcher applied qualitative method. In collecting the data the researcher used three procedures; interviewing recording and noting. Then the data was analyzed in three ways; data redaction, data display, and conclusion. The subject consists of 40 students from fifth semester. Finally, the researcher found that the strategies that the students used in learning communication are good. It means that the strategies may help them to improve their abilities in doing communication by English. It can be seen at finding of this study (chapter IV). The students? communication ability improves together with the process of teaching and learning in the class. There are some strategies that they used; confirmation check, clarification check, comprehension check, self-repetition. Through these strategies their mistake and also their selves-confident in expressing their ideas is better than before.